Simplify It

Algebra Level 4

1 + 1 1 2 + 1 2 2 + 1 + 1 2 2 + 1 3 2 + + 1 + 1 201 5 2 + 1 201 6 2 = ? \sqrt{1+\frac{1}{1^2} + \frac{1}{2^2} } + \sqrt{1+\frac{1}{2^2} + \frac{1}{3^2} } + \cdots + \sqrt{1+\frac{1}{2015^2} + \frac{1}{2016^2} } = \, ?

2016 1 2016 2016 - \frac{1}{2016} 2016 + 1 2016 2016 + \frac{1}{2016} 2015 1 2016 2015 - \frac{1}{2016} 2015 + 1 2016 2015 + \frac{1}{2016}

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Note that for any positive integer n n we have that

1 + 1 n 2 + 1 ( n + 1 ) 2 = n 2 ( n + 1 ) 2 + ( n + 1 ) 2 + n 2 n 2 ( n + 1 ) 2 = n 4 + 2 n 3 + 3 n 2 + 2 n + 1 n 2 ( n + 1 ) 2 = ( n 2 + n + 1 ) 2 n 2 ( n + 1 ) 2 1 + \dfrac{1}{n^{2}} + \dfrac{1}{(n + 1)^{2}} = \dfrac{n^{2}(n + 1)^{2} + (n + 1)^{2} + n^{2}}{n^{2}(n + 1)^{2}} = \dfrac{n^{4} + 2n^{3} + 3n^{2} + 2n + 1}{n^{2}(n + 1)^{2}} = \dfrac{(n^{2} + n + 1)^{2}}{n^{2}(n + 1)^{2}} ,

the square root of which is n 2 + n + 1 n ( n + 1 ) = 1 + 1 n ( n + 1 ) = 1 + ( 1 n 1 n + 1 ) \dfrac{n^{2} + n + 1}{n(n + 1)} = 1 + \dfrac{1}{n(n + 1)} = 1 + \left(\dfrac{1}{n} - \dfrac{1}{n + 1}\right) .

So the given sum, namely n = 1 2015 ( 1 + ( 1 n 1 n + 1 ) ) \displaystyle\sum_{n=1}^{2015}\left(1 + \left(\dfrac{1}{n} - \dfrac{1}{n + 1}\right)\right) telescopes to

2015 + ( 1 1 2016 ) = 2016 1 2016 2015 + \left(1 - \dfrac{1}{2016}\right) = \boxed{2016 - \dfrac{1}{2016}} .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...